Interaction of storage medium and silver diamine fluoride on demineralized dentin - Peng Jing-Yuan; Botelho Michael George; Matinlinna Jukka Pekka; Pan Hao-Bo; Kukk Edwin; Low Kam-Jung (SAGE PUBLICATIONS LTD, 2022)
Objective: The effects of saliva on demineralized dentin and silver diamine fluoride (SDF) were investigated in vitro.
Methods: Dentin samples stored in deionized water (DIW), buffer solution (BS), basal medium mucin (BMM), and unstimulated whole saliva (UWS) were demineralized for 3 days and immersed in the same storage media. SDF as a 38 mass% solution was applied to the dentin samples for 3 minutes after they had been replaced in their respective medium. Surfaces were analyzed by scanning electron microscopy, energy-dispersive X-ray analysis (EDX), X-ray photoelectron spectroscopy (XPS), and X-ray diffraction (XRD).
Results: Scanning electron microscopy showed various surface deposits and coatings, including occlusion of dentinal tubules. DIW resulted in the thinnest coating, whereas BMM resulted in the thickest. EDX and XPS showed the formation of metallic silver and silver compounds in all four media, with the greatest formation in BS. XRD indicated that the main product was silver chloride except in DIW. Sulphur was found in BMM and UWS. EDX and XPS detected fluoride and XRD detected calcium fluoride and fluorohydroxyapatite in BS, BMM, and UWS.ConclusionThe interaction between SDF and demineralized dentin was dependent upon the storage medium. BMM provided an outcome most similar to human saliva.